Determination of fetal thymic morphometric dimensions in relation to gestational age. - Carmen Niurka Piña Loyola; Marta Rosa González Debén; Alfredo Quiñonez Ceballo (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2010)
Background: the appropriate relationship between gestational age and fetal weight are variables that reflect the intrauterine development and fetal welfare. There are studies that have attempted to establish morphological patterns of the thymus in relation to gestational age and who report dissimilar values. Objective: To determine the morphometric dimensions of the thymus in relation to gestational age. Methods: A descriptive, observational case series conducted in the period May 2003 to May 2008 in General Hospital Universitario "Dr. Gustavo Lima Aldereguía "of Cienfuegos. The sample consisted of 147 scams dead fetuses from 17 weeks gestational age until the end, who met the inclusion criteria. Body measurements were made such as: weight, height, width, thickness and volume. Results: We observed a progressive increase of all the morphometric dimensions of the thymus in relation to higher gestational age, marked in the late fetal stage where the values are doubled. The weight, height and volume were lower thymic 80% of the sample. For 90% of cases the thickness of the organ was below 5 mm and width, regardless of gestational age was less than 20 mm by 50%, and the remaining 50% of 20-50 mm. Conclusions: determined morphometric dimensions of the thymus and showed a gradual increase of these in relation to gestational age and fetal weight.